2022
DOI: 10.2105/ajph.2022.307011
|View full text |Cite
|
Sign up to set email alerts
|

The 2016 Presidential Election, the Public Charge Rule, and Food and Nutrition Assistance Among Immigrant Households

Abstract: Objectives. To investigate whether the 2016 US presidential election and the subsequent leak of a proposed change to the public charge rule reduced immigrant families’ participation in food and nutrition assistance programs. Methods. We used nationally representative data on n = 57 808 households in the United States from the 2015–2018 Current Population Survey–Food Security Supplement. We implemented difference-in-difference-in-difference analyses to investigate whether the election and proposed rule change … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…While we did not have information about participants' immigration status, it is plausible that immigration influenced the study's urban, predominantly Spanishpreferring population. Threats of impending changes to policies affecting or affected by immigration status that occurred during the HASII study's enrollment period, such as those expected to the "public charge rule," negatively impacted enrollment in public assistance programs, including immigrant communities' enrollment in Medicaid (Bustamante et al, 2022;Miller et al, 2022;Wang et al, 2022). It is possible that fear associated with the public charge rule or other programse.g.…”
Section: Discussionmentioning
confidence: 99%
“…While we did not have information about participants' immigration status, it is plausible that immigration influenced the study's urban, predominantly Spanishpreferring population. Threats of impending changes to policies affecting or affected by immigration status that occurred during the HASII study's enrollment period, such as those expected to the "public charge rule," negatively impacted enrollment in public assistance programs, including immigrant communities' enrollment in Medicaid (Bustamante et al, 2022;Miller et al, 2022;Wang et al, 2022). It is possible that fear associated with the public charge rule or other programse.g.…”
Section: Discussionmentioning
confidence: 99%
“… 15 , 26 , 50 , 60 Other studies examining Trump's candidacy declaration and early rhetoric found a similar relationship with declining adult and child health care utilization and public-assistance enrollment among immigrant and mixed-status families in SNAP, the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC), school meals, and Medicaid. 8 , 15 , 16 , 18 , 19 It is in our national interest for all children and their families to be able to meet their basic needs, including for health care. Thus, it is important for candidates for public office, executive branch, legislative, health systems, and public health leaders to be mindful of the far-reaching physical and mental health consequences of the language and policy proposals our leaders choose to emphasize as well as the implementation of restrictive laws and policies.…”
Section: Discussionmentioning
confidence: 99%